Development of food safety module and sanitation management - Ahmad, Nor Aziah; Mohamad Sukeri, Siti Nur Sarini; Tukiran, Nor Anis Intan Aqiah; Zakariah, Siti Hajar; Ismail, Lisa Marian Syawal; Harun, Hairuddin; Md Sahak, Adibah Aishah; Abdul Rahman, Abdul Wafi (2021)
In the process of teaching and learning, teaching materials such as modules are tools of teaching aids that play an important role in achieving educational goals. The study was conducted to develop a study module of Food Safety and Sanitation Management for students taking catering courses at the Faculty Of Technical and Vocational Education at UTHM. In this study, the development of this module is based on the five phases of the ADDIE model consisting analysis, design, development, implementation, and evaluation. The development of this module will serve as a reference or guide for students taking catering courses. Subsequently, researchers have chosen to develop this module in English. Based on this module, researchers have also made improvements by adding subtopic to the content of this developed module. In addition, the researchers also developed this module by following the syllabus set by the faculty. Researchers have also obtained the approval of three experts who teach catering courses at the Faculty of Technical and Vocational Education (FPTV). The results show that all experts agree that this module can serve as a reference and a guide in teaching and learning. However, this module still needs to be improved to make it more interesting and interactive to engage students in learning.